Kondisi Sosial Ekonomi Masyarakat Sulawesi Selatan Pada Masa Gerakan Abdul Qahar Mudzakkar - Saputro, Pradata Ardi; Permana Putri, Vina (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The Abdul Qahar Mudzakkar movement in South Sulawesi between the 1950s and 1960s constituted one of the most prolonged armed rebellions in post-independence Indonesia, significantly affecting local socio-economic conditions. This study aims to analyze the social and economic impacts of the movement on South Sulawesi society, particularly in rural areas that became centers of conflict. Using a qualitative historical research design, this study employs document analysis of academic journals, dissertations, and historical records relevant to the DI/TII movement and regional socio-economic dynamics. The findings indicate that prolonged armed conflict led to severe disruption of agricultural production, damage to rural infrastructure, declining household incomes, increased poverty, and social stratification. The instability also weakened state services, reduced educational access, and intensified survival-based economic practices. Furthermore, socio-economic disparities reinforced local grievances that sustained the movement. This study contributes to the historiography of Indonesian regional conflicts by integrating socio-economic perspectives into the analysis of political rebellion. The findings underline the importance of socio-economic recovery and inclusive development in post-conflict regions.